# (b+4)(b+4)=100

## Simple and best practice solution for (b+4)(b+4)=100 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for (b+4)(b+4)=100 equation:

Simplifying
(b + 4)(b + 4) = 100
Reorder the terms:
(4 + b)(b + 4) = 100
Reorder the terms:
(4 + b)(4 + b) = 100
Multiply (4 + b) * (4 + b)
(4(4 + b) + b(4 + b)) = 100
((4 * 4 + b * 4) + b(4 + b)) = 100
((16 + 4b) + b(4 + b)) = 100
(16 + 4b + (4 * b + b * b)) = 100
(16 + 4b + (4b + b2)) = 100
Combine like terms: 4b + 4b = 8b
(16 + 8b + b2) = 100
Solving
16 + 8b + b2 = 100
Solving for variable 'b'.
Reorder the terms:
16 + -100 + 8b + b2 = 100 + -100
Combine like terms: 16 + -100 = -84
-84 + 8b + b2 = 100 + -100
Combine like terms: 100 + -100 = 0
-84 + 8b + b2 = 0
Factor a trinomial.
(-14 + -1b)(6 + -1b) = 0
Subproblem 1Set the factor '(-14 + -1b)' equal to zero and attempt to solve:
Simplifying
-14 + -1b = 0
Solving
-14 + -1b = 0
Move all terms containing b to the left, all other terms to the right.
Add '14' to each side of the equation.
-14 + 14 + -1b = 0 + 14
Combine like terms: -14 + 14 = 0
0 + -1b = 0 + 14
-1b = 0 + 14
Combine like terms: 0 + 14 = 14
-1b = 14
Divide each side by '-1'.
b = -14
Simplifying
b = -14
Subproblem 2Set the factor '(6 + -1b)' equal to zero and attempt to solve:
Simplifying
6 + -1b = 0
Solving
6 + -1b = 0
Move all terms containing b to the left, all other terms to the right.
Add '-6' to each side of the equation.
6 + -6 + -1b = 0 + -6
Combine like terms: 6 + -6 = 0
0 + -1b = 0 + -6
-1b = 0 + -6
Combine like terms: 0 + -6 = -6
-1b = -6
Divide each side by '-1'.
b = 6
Simplifying
b = 6Solutionb = {-14, 6}`

## Related pages

roman numeral 1991factors of 3136x 2-1 factoredsquare root of 43560square root of 4225subtracting fractions calculator9cxsimplify the square root of 1082x2 5x 3csc2 xderivatives of sin and cos2cosxsinxsimplify sinx cosxsolve xe xfractions least to greatest calculator9x 2-16derivative of 2xyfactor 5x 15what is 0.1875 as a fractionfactor tree of 125common multiples of 15what is 0.36 repeating as a fractionx 2 16xtan 4xprime factorization for 68derivative of 2sinxshow how to solve 3x 2 10x 8 by factoringx 6y 12sin 4x graphcos2x cos3xwhat is the lcm of 1573-100prime factorization of 98what is a prime factorization of 725 eighths as a percentderivative of tanx37.5-25fractions multiplication calculatorxx 4xy8 8ydecimal fraction percentage757-100what is the prime factorization for 98prime factorization of 2257x3.5prime factorization of 95roman numerals 1960adding mixed fractions calculatory mx b solverwhat is the prime factorization of 169multiples of 324roman numerals 1998273.15what is 77 in roman numerals100-76greatest common factor of 120derivative of 9x6x squared3 8ths of 24derivative of tan sinx126 prime factorizationfactorise x squared x3x 3y493.90prime factorization 360solving quadratic calculatorpercent to decimal calculatorcommon multiples of 4 and 8x2 3x 7 0simplify square root of 2882x 5y 12144-108prime factorization of 7875-30014x3dxm calculatorprime factorization of 1843x 2y 13 2x 3y 129x 2-165 k equals1981 in roman numerals